Factores psicosociales, procesamiento para el diagnóstico en los trabajadores(as) en las áreas de vinculación e investigación de la ESPAM MFL - Mora Zambrano, Silvia Patricia (2014)
Present work was realized in the research and community outreach units in the areas of livestock, agro-industry and agriculture of the ESPAM, it was held with the objective of determining psychosocial risk factors in workers and how affect their health, this was accomplished through the bibliographic search for different authors to give sustenance to the research, the design of a general procedure for the diagnosis of psychosocial risk factors, the application of the procedure and proposition of a program for improvements to eliminate or mitigate those factors present in the working activity. For the development of the work was survey tool was applied to three schools in the following detail: livestock with 62 workers, agribusiness and agricultural 12 and 26 workers. The evaluation of psychosocial risks factors were: double presence, decision making, job motivation, capacity of the leader, interpersonal relations, and labor unrest. The options were: always, often, sometimes, only once and never, in five situations, to make the diagnosis is established very unfavorable, unfavorable, intermediate, Pro and very favorable for harmful aspects in the health of workers. Once applied the survey it was determined the area with the highest rate of psychosocial risk the agro-industry school, where it denotes a greater percentage of risk that could be detrimental to workers if appropriate management measures are not taken.